THE LANGUAGE MAINTENANCE OF BALINESE IN LANGKAT - Ramadani Ramadani; Sumarsih Sumarsih; Busmin Gurning (LINGUISTIK TERAPAN, 2018)
This study deals with the language maintenance of Balinese in Langkat. This objective of the study was to examine the factors affecting the Balinese language maintenance in Langkat. This study was descriptively qulitatively conducted. The subjects taken were 20  males and females of Balinese. The use of instruments in this study were interview to gain the factors of Balinese language maintainance in Langkat. The theories of Holmes was used in this study. The data were analyzed by using Spradley analysis (1979). There are seven factors affecting Balinese language maintenance in the first and the second generation of Balinese in Langkat found as the findings of the study such as; ethno linguistic vitality, using language in family domain, using language in neighborhood domain, using language in religion domain, using language in workplace domain, practice of traditional ceremony and an additional factor that found by researcher as a new insight in this research is interaction with older people. Analysis of data clearly indicates that Balinese language maintenance were done in Langkat.Keywords: language maintenance, factors affecting language maintenance, Balinese in Langkat